2016
DOI: 10.1155/2016/3687420
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of T Cell FOXP3 and T-Bet Is Upregulated in Severe but Not Euthyroid Hashimoto’s Thyroiditis

Abstract: Hashimoto's thyroiditis (HT) is an organ-specific autoimmune disorder characterized by progressive thyroid failure. Th1 and Treg subset of CD4+ cells have been implicated in the pathogenesis; however, less is known about their respective roles across the spectrum of HT clinical presentations. To shed more light on CD4+ subsets role in HT, we investigated the mRNA expression levels of several Th1/Treg-associated transcription factors (T-bet/ETS1, HIF1α/BLIMP1/FOXP3) in peripheral blood T cells of 10 hypothyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 45 publications
(60 reference statements)
0
15
0
1
Order By: Relevance
“…26 However, another study demonstrated FOXP3 upregulation in the T cells of peripheral blood samples from patients with HT. 21 This discrepancy is perhaps attributable to differing inclusion criteria used in these studies. 21,35,36 In the current study, expression of the T-bet/ FOXP3, GATA 3 /FOXP3 and RORα/FOXP3 ratios was significantly increased among patients with HT in comparison with the healthy control group; however, while the expression of T-bet, GATA 3 and RORα alone was increased, FOXP3 expression alone was reduced among HT patients.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…26 However, another study demonstrated FOXP3 upregulation in the T cells of peripheral blood samples from patients with HT. 21 This discrepancy is perhaps attributable to differing inclusion criteria used in these studies. 21,35,36 In the current study, expression of the T-bet/ FOXP3, GATA 3 /FOXP3 and RORα/FOXP3 ratios was significantly increased among patients with HT in comparison with the healthy control group; however, while the expression of T-bet, GATA 3 and RORα alone was increased, FOXP3 expression alone was reduced among HT patients.…”
Section: Discussionmentioning
confidence: 97%
“…21 This discrepancy is perhaps attributable to differing inclusion criteria used in these studies. 21,35,36 In the current study, expression of the T-bet/ FOXP3, GATA 3 /FOXP3 and RORα/FOXP3 ratios was significantly increased among patients with HT in comparison with the healthy control group; however, while the expression of T-bet, GATA 3 and RORα alone was increased, FOXP3 expression alone was reduced among HT patients. Therefore, it is logical that expression of the T-bet/FOXP3, GATA 3 /FOXP3 and RORα/FOXP3 ratios was significantly increased among the HT patients.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations